MENGEMBANGKAN KETERAMPILAN MENGGUNTING DENGAN KOMBINASI MODEL PROJECT BASED LEARNING, DIRECT INSTRUCTION DAN MEDIA KERTAS BERGAMBAR - Anisa, Nor; Sulistiyana, Sulistiyana (ACTION : Jurnal Inovasi Penelitian Tindakan Kelas dan Sekolah, 2025)
This research is based on the low fine motor ability in scissors activities according to the pattern in Group B, the solution to solve this problem is by using a combination of Project Based Learning, Direct Instruction models with illustrated paper media. The purpose of this study is to describe teacher activities, children's activities and the results of children's fine motor development. The approach used is a qualitative approach with the type of Classroom Action Research (PTK) with 4 meetings. Data analysis showed that teachers' activities achieved a score of 40 with the criterion of "Excellent". The child's activity achieved a score of 90% with the criterion of "Very Active", and the results of fine motor development reached a score of 90% with the criterion of "Successfully Developing". Based on the results of the study, it can be concluded that the Project Based Learning, Direct Instruction model with illustrated paper media can increase teacher activities, children's activities, and children's fine motor development. So this research can make learning innovations in the selection of the right models and media to develop scissor skills according to patterns. ABSTRAK Penelitian ini dilatar belakangi oleh rendahnya kemampuan motorik halus pada kegiatan menggunting sesuai pola pada Kelompok B solusi pemecahan masalah ini yaitu dengan menggunakan kombinasi model Project Based Learning, Direct Instruction dengan media kertas bergambar. Tujuan dalam penelitian ini untuk mendeskripsikan aktivtas guru, aktivitas anak dan hasil perkembangan motorik halus. Pendekatan yang digunakan adalah pendekatan kualitatif dengan jenis Penelitian Tindakan Kelas (PTK) dengan 4 kali pertemuan. Analisis data menunjukkan bahwa aktivitas guru mencapai skor 40 dengan kriteria “Sangat Baik”. Aktivitas anak mencapai skor 90% dengan kriteria “Sangat Aktif”, dan hasil perkembangan motorik halus mencapai skor 90% dengan kriteria “Berhasil Berkembang”. Berdasarkan hasil penelitian dapat disimpulkan bahwa model Project Based Learning, Direct Instruction dengan media kertas bergambar dapat meningkatkan aktivitas guru, aktivtas anak, perkembangan motorik halus anak. Maka penelitian ini dapat menjadikan inovasi pembelajaran dalam pemilihan model serta media yang tepat untuk mengembangkan keterampilan menggunting sesuai pola.